Impacts of tobacco excise duty on consumers and producers in the Czech Republic - Kolářová, Eva; Homola, David (Adiktologie, 2020)
BACKGROUND: An excise tax on cigarettes is imposed by the vast majority of countries in the world. Cigarette smoking is generally considered harmful and states are interested in reducing it. At the same time, governments are gaining substantial revenues for the state budget from the taxation of cigarettes. The tax component amounts for a significant portion of the retail price of cigarettes, and the amount of excise duty can lead to tax avoidance by the tobacco producers, smuggling, or an increase in the illicit tobacco trade. All the organizations focusing on the reduction of smoking amongst the population are trying to find the ideal balance between available measures to maximize the positive effects on the population and the economy as well. AIM: This paper analyses the dependency between tobacco taxation and the prevalence of smoking in the Czech Republic. The paper also aims to verify a connection between tobacco taxation and an increase in the illicit tobacco trade. METHODS: The data under analysis is from the period between 2010 and 2019. The data for the Czech Republic is collected from national reports and databases. The data concerning comparative information from other European countries is gathered from the European Commission databases. Descriptive statistics, the Pearson correlation coefficient, and the paired t-test are used to test the respective hypotheses. RESULTS: The results confirm the existence of a weak dependency between the levels of excise duty and the number of smokers in the Czech Republic and we can conclude that increasing tobacco taxation can result in a decrease in the number of smokers in the population. Additionally, the hypothesis of a relationship between the occurrence of an illicit trade and the level of tobacco taxation was not proved. This finding indicates that increasing tobacco taxation does not significantly influence the occurrence of an illicit trade in the Czech Republic. CONCLUSIONS: The present paper adds to the existing literature on the topic of tobacco taxation and provides a conclusive summary of the effects of the taxation of tobacco on the prevalence of smoking in the Czech Republic. In the Czech Republic and other European countries, these findings can be utilized as support for planning future excise duty laws.